Die Rothschild'schen Gemäldesammlungen in Wien - Kunth, Felicitas (2006)
Emerging from the Jewish ghetto in Frankfurt, the Rothschilds took over in the world of banking in less than 50 years. In 1820, Salomon Rothschild came to Vienna to open a branch of the family banking house. His son Anselm was to make his name in the capital city of the Austrian monarchy not only as a financier but also as an art-collector: he laid the foundation for the significant art collections of the Viennese Rothschilds, which were extended and improved continuously, right through until 1938.